2011
DOI: 10.1007/s11262-011-0688-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of two type 6 echovirus (E6) strains recovered from sewage specimens in Greece in 2006

Abstract: Echovirus 6 (E6) is one of the main enteroviral serotypes that was isolated from cases of aseptic meningitis and encephalitis during the last years in Greece. Two E6 (LR51A5 and LR61G3) were isolated from the sewage treatment plant unit in Larissa, Greece, in May 2006, 1 year before their characterization from aseptic meningitis cases. The two isolates were initially found to be intra-serotypic recombinants in the genomic region VP1, a finding that initiated a full genome sequence analysis. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In previous studies, many serotypes of EV were reported of causing encephalitis outbreak in children, such as Echovirus 30 in Belgium, 2000, [ 20 ] Echovirus 6 in Greece, 2006, [ 21 ] Echovirus 4 in Spain, 2008, [ 22 ] Echovirus 19 in Uttar Pradesh, India, 2008, [ 23 ] Echovirus 9 in Sri Lanka, 2009, [ 24 ] and Coxsackievirus B5 in Henan, China [ 25 ] ; Echovirus 30 is a mostly common serotype in meningitis outbreaks caused by EV around the world. [ 26 ] According to the sequence of VP1 or 5′UTR, Echovirus 30 was found to be the major serotype in Hangzhou, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, many serotypes of EV were reported of causing encephalitis outbreak in children, such as Echovirus 30 in Belgium, 2000, [ 20 ] Echovirus 6 in Greece, 2006, [ 21 ] Echovirus 4 in Spain, 2008, [ 22 ] Echovirus 19 in Uttar Pradesh, India, 2008, [ 23 ] Echovirus 9 in Sri Lanka, 2009, [ 24 ] and Coxsackievirus B5 in Henan, China [ 25 ] ; Echovirus 30 is a mostly common serotype in meningitis outbreaks caused by EV around the world. [ 26 ] According to the sequence of VP1 or 5′UTR, Echovirus 30 was found to be the major serotype in Hangzhou, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The RF groups assigned were distinct from 3Dpol sequence groupings of the prototype Amori and Charles E6 isolates (AY302558 and AF465517), the recently described E6 variants in the C9c lineage associated with an outbreak of aseptic meningitis in Japan [AB705308–AB705311; Miyoshi et al, ] and the C7 lineage sequences from Greece [Kyriakopoulou et al, ]. 3Dpol sequences from E6 variants in the latter two studies fell into clades distinct from those of other E6 or species B serotypes.…”
Section: Resultsmentioning
confidence: 84%
“…In previous studies, many serotypes of EV were reported of causing encephalitis outbreak in children, such as Echovirus 30 in Belgium, 2000, [20] Echovirus 6 in Greece, 2006, [21] Echovirus 4 in Spain, 2008, [22] Echovirus 19 in Uttar Pradesh, India, 2008, [23] Echovirus 9 in Sri Lanka, 2009, [24] and Coxsackievirus B5 in Henan, China [25] ; Echovirus 30 is a mostly common serotype in meningitis outbreaks caused by EV around the world. [26] According to the sequence of VP1 or 5 0 UTR, Echovirus 30 was found to be the major serotype in Hangzhou, 2015.…”
Section: Eve (Average)mentioning
confidence: 99%